Analysis of Core Endurance and, Static and Dynamic Balance Relationship in Adolescent Athletes. - Akınoğlu, Bihter; Aras, Mukaddes; Hasanoğlu, Adnan; Kocahan, Tuğba (Hacettepe University Faculty of Health Sciences Journal)
Objectives: Core muscles are key components for improving sports performance and preventing injury. In addition, balance is known to have a significant effect on sports performance. This study focuses on how the static endurance of core muscles interact with the static and dynamic balance in adolescent athletes. Materials and Methods: 49 athletes [water polo (n=13), fencing (n=8) and swimming (n=28)] have participated in this study. Mc-Gill core endurance tests were used to evaluate the core muscles endurance. And, HUBER-360 device was used to evaluate the static and dynamic balance skills. Once the measurements were completed, Pearson or Spearman correlation test was used to assess the relationship between the collected data. Results: The results have revealed a moderately negative correlation between trunk flexion test and double-foot static balance test's eyes open area value (r =-0.427; p=0.002); and a weak negative correlation among the left bridge endurance test and the eyes open test and the left foot static balance test' area values (r=-0.306/-0.347; p<0.05). No relationship was observed between the core muscles endurance and the dynamic balance skills (p>0.05). Conclusion: Incorporating anterior core muscles endurance exercises into training regimens may be beneficial in improving static balance performance in adolescent athletes. However, it appears that the endurance of lateral and posterior trunk muscles is not associated with static and dynamic balance.